The Influence of Horse Assisted Education on the Perception of Self-Efficacy in People Holding Leadership Positions - Wojtkowska, Magdalena; Kaczmarek, Magdalena; Gazdowska, Zuzanna (Journal of Education, Health and Sport, 2019)
Introduction and purpose Self-efficacy is defined as an indicator of what a person thinks they can do in various circumstances (Bandura, 1997). The present study examines whether participation in Horse Assisted Education workshops dedicated to the development of leadership competencies contributed to changes in the perception of self-efficacy. Materials and methods This study uses the GSES along with the LSES scale, which was constructed for the purposes of this study to measure the perception of self-efficacy within four leadership functions (Griffin, 1984). The 24 study subjects participated in Horse Assisted Education leadership competency development workshops. Measurement with the use of questionnaires was carried out three times – prior to the workshop, after the workshop and two weeks after the workshop. Results No changes in terms of generalized perception of self-efficacy were shown in the first and the second measurement, whereas the third measurement showed a significant increase. Measurements performed with the LSES questionnaire showed an increase in the perception of self-efficacy in performing leadership functions immediately after the workshops. A detailed analysis of changes within each of the presented leadership functions showed growth in the perception of self-efficacy in the second measurement with regard to motivating skills, and in the third measurement – in relation to planning and organizing work, with no changes in terms of controlling skills. Conclusions The results of the present study show that Horse Assisted Education can be used as an effective tool to strengthen the perception of self-efficacy in leadership skills. It is necessary to conduct research that takes into account replication on a larger population, and to test the effectiveness of the method in other applications.